El método coerver y su incidencia en el desarrollo de habilidades y destrezas de los jugadores en la categoría sub 12 de la escuela de fútbol de la liga parroquial Belisario Quevedo. - Chimbo Ronquillo, Marco Fabián (2019)
The present work was focused on Coerver Method determined as technical training or training of technical foundations carried out in reduced spaces where the individual is the center of attention of football teaching in order to improve individual and Collectives skills on sub 12 category players of Belisario Quevedo parish league. When referring to the method, it can be determined that it is the feints, dribbles and feints made by the worldrenowned players. These movements are used to destabilize the opponent in their defensive task through technical movements with the ball at high speeds, to gain space and time and to be able to define in front of the rival portico in a few seconds and without haste. The elaboration of the document was based on a descriptive research with a non-experimental design based on a field work and the bibliographic and documentary collection of the information referring to Coerver Method and its incidence for skills and abilities development. The proper use of the Coerver Method will contribute significantly to the sequential motor development of adolescent and in the later of the young person where they will improve their individual technical aspects and improve the speed of their game with the ball in reduced spaces, and therefore at real game situations.